Coexistence of Giant Hydatid Cyst and Hepatocellular Carcinoma: A Case Report and Literature Review - Ismail Eren Birol; Sukru Salih Toprak; Fatih Gurel (Iranian Journal of Parasitology)
From a global perspective, hepatocellular carcinoma (HCC) and hydatid cyst disease are both common; however, the endemic and zoonotic nature of hydatid cysts (due to Echinococcus larvae) makes the simultaneous detection of the two conditions a rare occurrence. In this case report, in a 43-year-old male patient, we aim to draw attention to the potential coexistence of HCC and liver hydatid cysts by presenting a case in which HCC tissue was detected in the cyst wall—removed by emergency surgery due to cyst perforation. Hydatid lesions in the liver may exhibit tumor-like growth characteristics. Consequently, identifying a hydatid cyst concomitant with HCC can be challenging, particularly when HCC has developed within the cystic structure. Careful assessment of resected tissues and detailed diagnostic approaches can facilitate the identification of such cases, even if the risk of HCC in patients with hydatid cysts is marginal. It may be advisable to suggest periodic monitoring with HCC-related markers and liver imaging methods.